2011
DOI: 10.3945/jn.110.135988
|View full text |Cite
|
Sign up to set email alerts
|

Children Are Aware of Food Insecurity and Take Responsibility for Managing Food Resources

Abstract: Child food insecurity is measured using parental reports of children's experiences based on an adult-generated conceptualization. Research on other child experiences (e.g. pain, exposure to domestic violence) cautions that children generally best report their own experiences, and parents' reports of children's experiences may lack adequate validity and impede effective intervention. Because this may be true of child food insecurity, we conducted semistructured interviews with mothers, children (age 9-16 y), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
261
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(281 citation statements)
references
References 21 publications
15
261
0
5
Order By: Relevance
“…For instance, mothers report managing household food resources for the whole family, and cutting back how much they eat at times of food scarcity in order to protect children [23]. Children, however, report eating less when food runs low so that younger siblings and parents have enough to eat [48]. Each reporter may be accurately reporting their experience, and yet these reports lead to contradictory information about children's food insecurity.…”
Section: B) Practical Considerations For a Global Monitoring Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, mothers report managing household food resources for the whole family, and cutting back how much they eat at times of food scarcity in order to protect children [23]. Children, however, report eating less when food runs low so that younger siblings and parents have enough to eat [48]. Each reporter may be accurately reporting their experience, and yet these reports lead to contradictory information about children's food insecurity.…”
Section: B) Practical Considerations For a Global Monitoring Systemmentioning
confidence: 99%
“…To date there has been less extensive use of child self-report assessments of child food insecurity, but existing work supports the existence of common crosscultural domains. Studies in the United States and Venezuela both found that children experience awareness of food insecurity, including cognitive awareness, emotional or psychological awareness, and physical awareness [48,53]. There are also commonalities in how children take on responsibilities for managing food insecurity, including children's participation in parent-initiated strategies, and strategies that children initiate themselves.…”
Section: Common Domains Of Household Food Insecuritymentioning
confidence: 99%
See 3 more Smart Citations